2022
DOI: 10.1111/rec.13618
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community composition of translocated ancient woodland soil: a case study

Abstract: Soil translocation is an ecological habitat restoration technique, which consists of moving the entire topsoil from a donor site to a chosen receptor site. We investigated soil chemistry and microbiology changes three growing seasons after the salvage of semiancient woodland soil (0.94 ha) to a nearby receptor pasture due to road widening works (Kent, United Kingdom). We sampled (1) Intact woodland soils adjacent to the area of soils that was translocated to represent the lost donor site; (2) The soil from thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Here, soil moisture, pH and TP are the most critical factors influencing the rare and abundant bacterial subcommunity diversity and structure in woodland soils. pH is closely correlated with microbial community composition in woodland soils (Borchers et al, 2022). Additionally, an earlier study reported that TN and pH affected the abundant bacterial subcommunity composition, whereas organic carbon shapes the rare bacterial subcommunity composition in oil-contaminated soils (Jiao et al, 2017).…”
Section: Stronger Linkage Between Rare Bacterial Diversity and Carbon...mentioning
confidence: 88%
“…Here, soil moisture, pH and TP are the most critical factors influencing the rare and abundant bacterial subcommunity diversity and structure in woodland soils. pH is closely correlated with microbial community composition in woodland soils (Borchers et al, 2022). Additionally, an earlier study reported that TN and pH affected the abundant bacterial subcommunity composition, whereas organic carbon shapes the rare bacterial subcommunity composition in oil-contaminated soils (Jiao et al, 2017).…”
Section: Stronger Linkage Between Rare Bacterial Diversity and Carbon...mentioning
confidence: 88%